Allometric models to estimate aboveground biomass in a Tectona grandis L. F. plantation in Yucatán - Marroquín-Morales, Pablo; Jiménez-Pérez, Javier; Yerena-Yamallel, José Israel; Reyes-Reyes, Jorge (Ecosistemas y Recursos Agropecuarios, 2023)
Allometric models are of vital importance since they allow estimating the aerial biomass in each of its components (leaves, branches, stem and total) of the tree. The objective of the study was to adjust allometric models to estimate aerial biomass by components in individual trees of Tectona grandis L. f. in Tizimin, Yucatan. Aerial biomass was estimated using the direct method, a total of 32 individuals were shot down in the field, each tree was separated by component; leaves, branches and stem and the green weight was determined, subsamples of the components were extracted to determine the dry weight-green weight relationship. To obtain the biomass, the total green weight of each component was multiplied by its corresponding ratio. Linear and non-linear equations were adjusted for each component, using the method of ordinary least squares. The non-linear (potential) model showed a better fit, presenting the stem and total component they registered an R2 of 0.96 in T. grandis L. f. The proportion of biomass in each of its components was different, being the stem the one with the highest percentage with 48%, followed by branches with 35 and 17% leaves.
Keywords: adjustment; biomass components; diameter; stem; teak